Selective Additives for Improvement of Gasoline Octane Number - Adel S. Hamadi (Tikrit Journal of Engineering Sciences, 2010)
High octane blend base gasoline stocks are reformulated from 30% LSRN, 45% Reformate and 25% Powerformate on volume basis. ASTM standard and IROX 2000 analysis are performed to test blend stocks sample. Different additive types are used to improve octane number. These additives are tetraethyl lead, methylcyclopentadienyl manganese tricarbonyl; methyl alcohol, ethyl alcohol, iso-propanol, n-butanol, sec-butanol, tertiary butyl alcohol, tert-amyl alcohol, active amyl alcohol, iso-pentyl alcohol, isobutyl carbinol, benzol ,telone, xylene, amino benzene, N-N-dimethyl aniline, dimethyl ketone, and ethyl methyl ketone. Comparison is made between significant individual RON gains measured by standard CFR test-engine. The results indicated that the combined iso-propanol, oxinol (50/50 blend of methanol and TBA), aniline, and xylene with hydrocarbons fraction content in the gasoline base pool is better to ensure high RON. The results showed that a mixture of 20/54/10/16 of blend aniline/ iso-propanol/ oxinol/ xylene respectively, led to an increase in RON of gasoline blend pool from 84.5 to 96 RON, or 11.5% RON gain.